Cultura pictórica e o percurso da quadratura no arraial do Tijuco no Século XVIII: entre o decorativo e a persuasão - Maria Cláudia Almeida Orlando Magnani (2013)
This research has a basic question: the paintings in churches in the Arraial do Tijuco the eighteenth century are merely ornamental or deliberately persuasive? In order to sustain the response that are deliberately persuasive. I opt for an understanding of the Baroque (the rebirth of its precursor) as a privileged moment in the persuasive function of art, precisely because it is a deliberate persuasion. Without reducing the baroque to this, I recall the persuasive function of counter-reform . This persuasion also understood as a demand of society that enjoys art. So, I try to understand in a comprehensive way the fabric mesh of corporate time of the Baroque in Europe, in Portugal and Brazil. And then specifically in Minas Gerais and Tijuco (who maintained a special relationship with the Crown).I present the third orders, brotherhoods and fraternities which played a specific main role in relation to art in Tijuco. With the identification of persuasive elements (such as the false architecture, paintings counters scenic and tissues which refer to the use of theater and Sibyls have historically been resumed at different times as persuasive elements), I try to understand and contextualize the figure of Braga's painter who brought the Tijuco the feigned architecture ,working with the hypothesis that he was actually a kind of a painting company and a complete artist. I demonstrate - with elements of his painting - the possible influence of some treaties like Andrea Pozzo in Tijuco.